Online Platform of Mathematical Terms in Karakalpak Language - Allabay, Arziev; Jumabek, Seypullayev; Purxan, Nasirov; Begench, Geldibayev (SOTVI, 2024)
The paper is devoted to the creation of an online platform of mathematical terms in Karakalpak language and its importance for education, cultural heritage and development of scientific research in Karakalpakstan. The platform provides access to a rich base of mathematical terminology in the native language, which facilitates the learning and teaching of mathematics for Karakalpak students and teachers. It contributes to the preservation of cultural values, enriches linguistic resources and stimulates scientific cooperation in the field of mathematics. The creation of this platform emphasizes the importance of linguistic diversity and cultural identity in the context of scientific and educational progress.